Special economic zones in India : policy, performance and prospects - Tantri, Malini L. (New York : Cambridge University Press, 2016)
""Discusses different aspects of Special Economic Zones ranging from its history to performance in India"--Provided by publisher"--
Includes bibliographical references (pages 155-167) and index.
Keywords: Economic zones -- India